A Systematic Review of the Burden of Multidrug-Resistant Healthcare-Associated Infections Among Intensive Care Unit Patients in Southeast Asia: The Rise of Multidrug-Resistant Acinetobacter baumannii. (27th March 2018) - Teerawattanapong, Nattawat; Panich, Pornpansa; Kulpokin, Disorn; Na Ranong, Siriwat; Kongpakwattana, Khachen; Saksinanon, Atibodi; Goh, Bey-Hing; Lee, Learn-Han; Apisarnthanarak, Anucha; Chaiyakunapruk, Nathorn
Abstract : OBJECTIVE: To summarize the clinical burden (cumulative incidence, prevalence, case fatality rate and length of stay) and economic burden (healthcare cost) of healthcare-associated infections (HAIs) due to multidrug-resistant organisms (MDROs) among patients in intensive care units (ICUs) in Southeast Asia. DESIGN: Systematic review. METHODS: We conducted a comprehensive literature search in PubMed, EMBASE, CINAHL, EconLit, and the Cochrane Library databases from their inception through September 30, 2016. Clinical and economic burdens and study quality were assessed for each included study. RESULTS: In total, 41 studies met our inclusion criteria; together, 22, 876 ICU patients from 7 Southeast Asian countries were included. The cumulative incidence of HAI caused by A. baumannii (AB) in Southeast Asia is substantially higher than has been reported in other regions, especially carbapenem-resistant AB (CRAB; 64.91%) and multidrug-resistant AB (MDR-AB) (58.51%). Evidence of a dose–response relationship between different degrees of drug resistance and excess mortality due to AB infections was observed. Adjusted odds ratios were 1.23 (95% confidence interval [CI], 0.51–3.00) for MDR-AB, 1.72 (95% CI, 0.77–3.80) for extensively drug-resistant AB (XDR-AB), and 1.82 (95% CI, 0.55–6.00) for pandrug-resistant AB (PDR-AB). There is, however, a paucity of published data on additional length of stay and costs attributable to MDROs. CONCLUSIONS: This review highlights the challenges in addressing MDROs in Southeast Asia, where HAIs caused by MDR gram-negative bacteria are abundant and have a strong impact on society. With our findings, we hope to draw the attention of clinicians and policy makers to the problem of antibiotic resistance and to issue a call for action in the management of MDROs. Infect Control Hosp Epidemiol 2018;39:525–533